The Effect of Meal Plan Diet & Daily Exercises Towards Stability of Cholesterol, Blood Pressure, Blood Sugar, Urid Acid, IMT Within Prevent Syndrome Metabolic - Salsabilla Adzani Rosma; Deden Akbar Izzuddin; R. Retna Kinanti Dewi; Saryono Saryono; Habibi Hadi Wijaya (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This research experienced differences among cholesterol, blood pressure, blood sugar, urid acid, and IMT after the sample did daily exercises and meal plan diet within 16 times mets. The type of this research is experiments with a quantitative approach and one group pretest-posttest design. The population was 25 women and 15 samples using a purposive sampling technique. The instrument test uses body scales, measurement straps, and Elvasense 3 in 1. The data analysis technique uses the normality test, homogeneity test, and paired t-test with SPSS IBM 21. The result from the normality test is p>0,05, and the result of the homogeneity test is sig>0,05 which means the data are homogeneous, except blood pressure which had the result of 0,015 which means non-homogeneous. The result of the paired t-test is significant with 0,000 < 0,05, the the result shows that there is a significant difference. The conclusion is there are effects of a meal plan diet & daily exercises towards preventive metabolic syndrome.